CS 332: Algorithms: Merge Sort Solving Recurrences The Master Theorem
CS 332: Algorithms: Merge Sort Solving Recurrences The Master Theorem
Merge Sort
Solving Recurrences
The Master Theorem
David Luebke 1
12/08/21
Administrative Question
Who here cannot make Monday-Wednesday
office hours at 10 AM?
If nobody, should we change class time?
David Luebke 2
12/08/21
Homework 1
Homework 1 will be posted later today
(Problem with the exercise numbering, sorry)
Due Monday Jan 28 at 9 AM
Should be a fairly simple warm-up problem set
David Luebke 3
12/08/21
Review: Asymptotic Notation
Upper Bound Notation:
f(n) is O(g(n)) if there exist positive constants c
and n0 such that f(n) c g(n) for all n n0
Formally, O(g(n)) = { f(n): positive constants c
and n0 such that f(n) c g(n) n n0
Big O fact:
A polynomial of degree k is O(nk)
David Luebke 4
12/08/21
Review: Asymptotic Notation
Asymptotic lower bound:
f(n) is (g(n)) if positive constants c and n0 such
that 0 cg(n) f(n) n n0
Asymptotic tight bound:
f(n) is (g(n)) if positive constants c1, c2, and n0
such that c1 g(n) f(n) c2 g(n) n n0
f(n) = (g(n)) if and only if
f(n) = O(g(n)) AND f(n) = (g(n))
David Luebke 5
12/08/21
Other Asymptotic Notations
A function f(n) is o(g(n)) if positive
constants c and n0 such that
f(n) < c g(n) n n0
A function f(n) is (g(n)) if positive
constants c and n0 such that
c g(n) < f(n) n n0
Intuitively,
o() is like < () is like > () is like =
O() is like () is like
David Luebke 6
12/08/21
Merge Sort
MergeSort(A, left, right) {
if (left < right) {
mid = floor((left + right) / 2);
MergeSort(A, left, mid);
MergeSort(A, mid+1, right);
Merge(A, left, mid, right);
}
}
David Luebke 7
12/08/21
Merge Sort: Example
Show MergeSort() running on the array
A = {10, 5, 7, 6, 1, 4, 8, 3, 2, 9};
David Luebke 8
12/08/21
Analysis of Merge Sort
Statement Effort
MergeSort(A, left, right) { T(n)
if (left < right) { (1)
mid = floor((left + right) / 2); (1)
MergeSort(A, left, mid); T(n/2)
MergeSort(A, mid+1, right); T(n/2)
Merge(A, left, mid, right); (n)
}
}
So T(n) = (1) when n = 1, and
David Luebke 9
12/08/21
Recurrences
The expression:
c n 1
T ( n)
2T cn n 1
n
2
is a recurrence.
Recurrence: an equation that describes a function in
terms of its value on smaller functions
David Luebke 10
12/08/21
Recurrence Examples
0 n0 0 n0
s ( n) s ( n)
c s (n 1) n 0 n s (n 1) n 0
n 1
c c n 1
T ( n) T ( n)
2T c n 1
n n
2 aT cn n 1
b
David Luebke 11
12/08/21
Solving Recurrences
Substitution method
Iteration method
Master method
David Luebke 12
12/08/21
Solving Recurrences
The substitution method (CLR 4.1)
A.k.a. the “making a good guess method”
Guess the form of the answer, then use induction
to find the constants and show that solution works
Examples:
T(n) = 2T(n/2) + (n) T(n) = (n lg n)
T(n) = 2T(n/2) + n ???
David Luebke 13
12/08/21
Solving Recurrences
The substitution method (CLR 4.1)
A.k.a. the “making a good guess method”
Guess the form of the answer, then use induction
to find the constants and show that solution works
Examples:
T(n) = 2T(n/2) + (n) T(n) = (n lg n)
T(n) = 2T(n/2) + n T(n) = (n lg n)
T(n) = 2T(n/2 )+ 17) + n ???
David Luebke 14
12/08/21
Solving Recurrences
The substitution method (CLR 4.1)
A.k.a. the “making a good guess method”
Guess the form of the answer, then use induction
to find the constants and show that solution works
Examples:
T(n) = 2T(n/2) + (n) T(n) = (n lg n)
T(n) = 2T(n/2) + n T(n) = (n lg n)
T(n) = 2T(n/2+ 17) + n (n lg n)
David Luebke 15
12/08/21
Solving Recurrences
Another option is what the book calls the
“iteration method”
Expand the recurrence
Work some algebra to express as a summation
Evaluate the summation
We will show several examples
David Luebke 16
12/08/21
0 n0
s ( n)
c s (n 1) n 0
s(n) =
c + s(n-1)
c + c + s(n-2)
2c + s(n-2)
2c + c + s(n-3)
3c + s(n-3)
…
kc + s(n-k) = ck + s(n-k)
David Luebke 17
12/08/21
0 n0
s ( n)
c s (n 1) n 0
So far for n >= k we have
s(n) = ck + s(n-k)
What if k = n?
s(n) = cn + s(0) = cn
David Luebke 18
12/08/21
0 n0
s ( n)
c s (n 1) n 0
So far for n >= k we have
s(n) = ck + s(n-k)
What if k = n?
s(n) = cn + s(0) = cn
So 0 n0
s ( n)
c s (n 1) n 0
Thus in general
s(n) = cn
David Luebke 19
12/08/21
0 n0
s ( n)
n s (n 1) n 0
s(n)
= n + s(n-1)
= n + n-1 + s(n-2)
= n + n-1 + n-2 + s(n-3)
= n + n-1 + n-2 + n-3 + s(n-4)
= …
= n + n-1 + n-2 + n-3 + … + n-(k-1) + s(n-k)
David Luebke 20
12/08/21
0 n0
s ( n)
n s (n 1) n 0
s(n)
= n + s(n-1)
= n + n-1 + s(n-2)
= n + n-1 + n-2 + s(n-3)
= n + n-1 + n-2 + n-3 + s(n-4)
= …
= n + n-1 + n-2 + n-3 + … + n-(k-1) + s(n-k)
n
i
i n k 1
s(n k )
David Luebke 21
12/08/21
0 n0
s ( n)
n s (n 1) n 0
So far for n >= k we have
n
i
i n k 1
s(n k )
David Luebke 22
12/08/21
0 n0
s ( n)
n s (n 1) n 0
So far for n >= k we have
n
i
i n k 1
s(n k )
What if k = n?
David Luebke 23
12/08/21
0 n0
s ( n)
n s (n 1) n 0
So far for n >= k we have
n
i
i n k 1
s(n k )
What if k = n?
n
n 1
n
i 1
i s (0) i 0 n
i 1 2
David Luebke 24
12/08/21
0 n0
s ( n)
n s (n 1) n 0
So far for n >= k we have
n
i
i n k 1
s(n k )
What if k = n?
n
n 1
n
i 1
i s (0) i 0 n
i 1 2
Thus in general
n 1
s ( n) n
2
David Luebke 25
12/08/21
c n 1
n
T (n) 2T
c n 1
2
T(n) =
2T(n/2) + c
2(2T(n/2/2) + c) + c
22T(n/22) + 2c + c
22(2T(n/22/2) + c) + 3c
23T(n/23) + 4c + 3c
23T(n/23) + 7c
23(2T(n/23/2) + c) + 7c
24T(n/24) + 15c
…
2kT(n/2k) + (2k - 1)c
David Luebke 26
12/08/21
c n 1
n
T (n) 2T
c n 1
2
So far for n > 2k we have
T(n) = 2kT(n/2k) + (2k - 1)c
What if k = lg n?
T(n) = 2lg n T(n/2lg n) + (2lg n - 1)c
= n T(n/n) + (n - 1)c
= n T(1) + (n-1)c
= nc + (n-1)c = (2n - 1)c
David Luebke 27
12/08/21